In the realm of gods and kings arts of India - Topsfield, Andrew (London Philip Wilson Publishers New York Distributed in North America by Palgrave Macmillan, 2013)
"This corrected and updated volume celebrates the wealth and diversity of the arts of India created for the life of courts and temples from 1000 bc to twentieth century, 112 paintings, 59 objects and 21 photographs ranging in date from the second century bc to the late twentieth century reflect the variety and continuities of India's aesthetic traditions." -- Provided by publisher
Art works from the Cynthia Hazen Polsky collection and the Metropolitan Museu of Art, New York.
Includes bibliographical references (pages 407-410) and index.
Keywords: Art, Indic -- Catalogs; Hindu gods in art -- Catalogs; Kings and rulers in art -- Catalogs